Am I My Peers’ Keeper? Problems of Professional Competency in Doctoral Students - Kathleen Brown-Rice; Susan Furr (Teaching and Supervision in Counseling, 2019)
Addressing problems of professional competency (PPC) among doctoral students is essential given that doctoral students will become our future counselor educators. In this study, doctoral students (N = 345) in CACREP-accredited programs were surveyed about their knowledge of peers’ PPC. The findings of this study indicate doctoral students are aware of peers with PPC (68.1%), which include inadequate skills to deliver counseling services as well as problematic behaviors related to personal or psychological issues. Findings suggest respondents are affected negatively by being in a program with a peer they perceive has a PPC (47.9%) and are frustrated with educators for allowing problematic peers to continue their doctoral training (70%). The findings of this study show that faculty members need to place more emphasis on educating doctoral students about competency issues and assessing for PPC.
Keywords: doctoral students; CACREP; problems of professional competency; peers; doctoral training